Implementasi Marketing Syari’ah dalam Perspektif Ekonomi Islam pada Wisma Barokah Syari’ah Tebing Tinggi - Gunawan, Tony; Amalia, Alfi (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Shari'ah marketing is a strategic business discipline that directs the process of creating, offering, and changing value from initiator to its stakeholders in the entire process there are values that are in accordance with the principles of shari'ah, namely the principles of tawhid, justice, free will, and responsibility. This research is a type of qualitative research that aims to determine the shari'ah marketing strategy applied by the tenggi cliff barokah barokah guesthouse and to find out the implementation of shari'ah marketing principles at the tenggi cliff barokah barokah guesthouse. The results of this study stated that the implementation of shari'ah marketing principles at Wisma Barokah Syari'ah Tebing Tinggi, namely the principle of tawhid, the principle of fairness, the principle of free will and the principle of responsibility has been carried out well and has been in accordance with the Sharia Economic Perspective. However, in the principle of tawhid, the guest house is not optimal in applying it because there are still visitor complaints about the absence of Islamic nuances in the hotel lobby such as calligraphy ornaments and in hotel rooms the unavailability of prayer mats and mukenah for visitors to pray in the room for the reason of the guesthouse is to invite visitors to pray in congregation at the mushoalah, of course this actually violates the principles of shari'ah marketing, especially in terms of the ease of consumers in getting closer to Allah.